(untitled) (Diametros, 2010)
There is a nonabsolute or “contingent” form of pacifism that claims that war in contemporary conditions inevitably involves the killing of innocent people on a scale that is too great to be justified. Some contingent pacifists argue that war always involves a risk that virtually everyone that one might kill is innocent – either because one can never be sure that one’s cause is just or because even most of those who fight in wars that lack a just cause are nevertheless not culpable and are therefore innocent in the relevant sense. Others argue that there is no just cause for war that is sufficiently important to justify the large-scale killing of innocent civilians that is unavoidable in war. I seek to refute contingent pacifism by arguing that its theoretical presuppositions are untenable.